Developing oxygen-enhanced magnetic resonance imaging as a prognostic biomarker of radiation response. Issue 1 (28th September 2016) - White, Derek A.; Zhang, Zhang; Li, Li; Gerberich, Jeni; Stojadinovic, Strahinja; Peschke, Peter; Mason, Ralph P.
Highlights: Hypoxia is associated with radiation resistance, particularly for SBRT. Non-invasive OE-MRI is a potential biomarker to predict tumor response. Breathing oxygen enhanced radiation response, with a wide range of responses. OE-MRI demonstrates a correlation between T1 -weighted contrast and radiation response. OE-MRI is highly translational. Abstract: Oxygen-Enhanced Magnetic Resonance Imaging (OE-MRI) techniques were evaluated as potential non-invasive predictive biomarkers of radiation response. Semi quantitative blood-oxygen level dependent (BOLD) and tissue oxygen level dependent (TOLD) contrast, and quantitative responses of relaxation rates (ΔR1 and ΔR2 *) to an oxygen breathing challenge during hypofractionated radiotherapy were applied. OE-MRI was performed on subcutaneous Dunning R3327-AT1 rat prostate tumors ( n   =   25 ) at 4.7 T prior to each irradiation (2F × 15 Gy) to the gross tumor volume. Response to radiation, while inhaling air or oxygen, was assessed by tumor growth delay measured up to four times the initial irradiated tumor volume (VQT). Radiation-induced hypoxia changes were confirmed using a double hypoxia marker assay. Inhaling oxygen during hypofractionated radiotherapy significantly improved radiation response. A correlation was observed between the difference in the 2nd and 1st ΔR1 (ΔΔR1 ) and VQT for air breathing rats. The TOLD response before the 2nd fraction showed a moderate correlation with VQT for oxygen breathing rats. The correlations indicate useful prognostic factors to predict tumor response to hypofractionation and could readily be applied for patient stratification and personalized radiotherapy treatment planning.